2012
DOI: 10.1111/j.1532-5415.2012.03927.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Gait Velocity in an Urban Elderly Cohort

Abstract: Background/ Objectives Gait Velocity (GV) is predictive of hospitalizations and mortality in the elderly. In the US, elderly African Americans have higher rates of physical disability compared to Caucasians. Few studies have investigated if there are racial differences in GV in the elderly. Design We performed a cross sectional analysis to investigate racial differences in GV. Setting/Participants Participants were part of the Einstein Aging Study, a longitudinal study of community-residing elderly in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…We did not observe racial differences in gait speed. However, a recent study [21] that compared Caucasians and African Americans identified that gait speed was slower in African Americans, even when adjusting for multiple confounders and covariates, such as age, gender, education, comorbidities and pain. One possible explanation is that, in some multiracial samples, such as ours, the ambiguity in racial classification can be substantial [36], mainly in Brazil where race is based primarily on skin colour rather than ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe racial differences in gait speed. However, a recent study [21] that compared Caucasians and African Americans identified that gait speed was slower in African Americans, even when adjusting for multiple confounders and covariates, such as age, gender, education, comorbidities and pain. One possible explanation is that, in some multiracial samples, such as ours, the ambiguity in racial classification can be substantial [36], mainly in Brazil where race is based primarily on skin colour rather than ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Mean values for usual gait speed in community-dwelling older adults vary substantially; for example, from 0.56 m/s in a Hispanic American population to 1.19 m/s in a population of men (mainly White Americans) [2]. These differences in walking speed may reflect not only a multi-systemic impairment in health status, traduced by biological dysfunctions (for example, cognitive, musculoskeletal, neural) such as dynapenia [17], diminished cutaneous sensitivity and decreased nerve conduction velocity [18] and brain neuronal loss and presence of white matter lesions [19,20], but may be also influenced by racial differences [21], psychological and socioeconomic conditions such as a high concern about falling [22], low educational level [23] and low employment grade [24]. Therefore, social, biological or health factors might explain why certain groups tend to self-select their gait speed (e.g., usual or fast) in different patterns, but the significance of each factor within a multifactorial approach has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…A velocidade de deslocamento tem sido descrita como um dos melhores indicadores de segurança na marcha. Incrementos em torno de 0,1 m.s -1 na velocidade de deslocamento de idosos estão diretamente associados com a redução do risco de acidentes durante a transposição de terrenos planos (41). Acredita-se que, de forma similar ao que acontece em terreno plano, incrementos na velocidade de deslocamento na rampa sejam reflexo de maior capacidade de controle.…”
Section: Resultsunclassified
“…Previous studies have also demonstrated lower physical function and greater disability in AA compared to EA. 32,33 Potentially, higher levels of inflammation among AA could contribute to disparities in physical function.…”
Section: Discussionmentioning
confidence: 99%